2018
DOI: 10.1159/000490807
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Pathways Drive Necroinflammation during Acute Kidney Injury

Abstract: Renal tubules represent an intercellular unit and function as a syncytium. When acute tubular necrosis was first visualized to occur through a process of synchronized regulated necrosis (SRN) in handpicked primary renal tubules, it became obvious that SRN actually promotes nephron loss. This realization adds to our current understanding of acute kidney injury (AKI)-chronic kidney disease (CKD) transition and argues for the prevention of AKI episodes to prevent CKD progression. Because SRN is triggered by necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…We also identify hsa-miR-500a-3P directly target the 3'UTR of MLKL, thereby alleviates kidney injury via limiting necroptosis 41. Compared with apoptosis, necroptosis incurs more severe consequence because cells suffered necroptosis release endogenous pro-inflammatory molecules like damage-associated molecular patterns (DAMPs) and promote renal inflammation 42, 43. In the current study, our results showed that loss of Smad2 prevented, but overexpression of Smad2 promoted, cisplatin-activated necroptotic signaling, this result indicates Smad2 may play an important role in mediating cell necroptosis and consequent necroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We also identify hsa-miR-500a-3P directly target the 3'UTR of MLKL, thereby alleviates kidney injury via limiting necroptosis 41. Compared with apoptosis, necroptosis incurs more severe consequence because cells suffered necroptosis release endogenous pro-inflammatory molecules like damage-associated molecular patterns (DAMPs) and promote renal inflammation 42, 43. In the current study, our results showed that loss of Smad2 prevented, but overexpression of Smad2 promoted, cisplatin-activated necroptotic signaling, this result indicates Smad2 may play an important role in mediating cell necroptosis and consequent necroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between ferroptosis and inflammation is also a hot research topic. Necrotic inflammation associated with ferroptosis has been observed in the kidneys in an AKI model induced by crystal (oxalate) and folic acid and in a GPX4 deletion mouse model 88 . Studies have found that GPX4 activation inhibits the activation of the arachidonic acid (AA) and nuclear factorkappa B (NF-κ B) pathways in the lipid peroxidationmediated inflammatory response, thereby reducing ROS levels in cells and inhibiting ferroptosis 89 .…”
Section: Ferroptosis and Other Diseasesmentioning
confidence: 99%
“…The specific molecular mechanism is still unclear 4 . Increasing evidence shows that ferroptosis can be accompanied by inflammation, and that cells can activate innate immune system factors through ferroptosis stimulation and play a role in regulating inflammation damage, signal transduction, and cell growth 88,89 . Some studies have found that GPX4 activation can be used as a new anti-inflammatory or cytoprotective therapy 89 , but how can ferroptosis promote the development of inflammation?…”
Section: Issues and Prospectsmentioning
confidence: 99%
“…The initial wave of tubular cell death is followed by tubular cell proliferation favoring regeneration, and by a second wave of cell death that adjusts the final cell number [5,6]. Regulated necrosis cell death through ferroptosis and necroptosis releases inflammatory cytokines that amplify tissue injury [7,8] while there is also evidence for a contribution of apoptotic cell death to kidney injury [9].…”
Section: Aki Ckd and The Mitochondrial Connectionmentioning
confidence: 99%